Seasonal variation of water table and groundwater quality of the karst aquifer of the Jaffna Peninsula – Sri Lanka - Joshua, W.D.; Thushyanthy, M.; Nanthagoban, N. (Journal of the National Science Foundation of Sri Lanka. 2013, 2013)
The Miocene limestone bedrock of the Jaffna P eninsula of Sri Lanka extends below the sea level and is an excellent aquifer. The North-East Monsoonal rainfall infiltrates into the soil and forms a layer of fresh water in the limestone above the seawater. This freshwater is in the form of a convex lens, which thins out towards coast and the lower part of the lens is a transitional zone where the freshwater becomes increasingly brackish with depth. The thickness of the lens diminishes continuously due to the outflow of freshwater into the lagoon/sea along the coastline. Even with this outflow, the freshwater in the lens is able to sustain irrigation and domestic usage till the end of the dry season. The groundwater has an abundance of calcium and bicarbonate ions, the varying concentrations of which affects the pH, causing it to vary from neutral to slightly alkaline. The concentrations of chloride ions increase with the depth of the transition zone as well as towards the coast. The nitrate contents of the well water are higher in the urban areas due to contamination from septic tanks and also intensively cultivated farm areas where high amounts of nitrogen fertilizers are used. In some wells, both the chloride and nitrate concentrations do exceed the WHO standards for safe drinking water. Thus, the quality of well water is site specific depending on the depth of wells in relation to the transition zone and the surrounding environment.
Keywords: Ground Water; Limestone Aquifer; Water Quality; Water Table